2020
DOI: 10.5435/jaaosglobal-d-20-00081
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Disability Assessment Among Hispanics With Zone 2 Flexor Tendon Injuries: Comparative Study Between Flexor Digitorum Superficialis Repair and Flexor Digitorum Superficialis Excision

Abstract: Introduction: Flexor tendon lacerations in zone II have been reported to be the most complicated of all tendon injuries. Currently, there is no consensus on treatment in surgical management for patients with flexor tendon laceration of flexor digitorum profundus and flexor digitorum superficialis (FDS). The aim of this study was to evaluate whether the repair of FDS tendons provided superior functional outcomes compared with FDS excision in Hispanic patients. Methods: Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[3][4][5][6][7] Restoration of movement and function after flexor tendon repair remains a challenge, particularly for zone II injuries. 8,9 Rehabilitation must find the balance of protecting the repair site from attenuation or rupture, while also enabling sufficient movement and tendon glide to prevent scar adhesions and joint contractures.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Restoration of movement and function after flexor tendon repair remains a challenge, particularly for zone II injuries. 8,9 Rehabilitation must find the balance of protecting the repair site from attenuation or rupture, while also enabling sufficient movement and tendon glide to prevent scar adhesions and joint contractures.…”
Section: Introductionmentioning
confidence: 99%
“…We found a statistically significant relationship between pain during motion and the DASH up to one year after flexor tendon repair, while pain at rest did not show any association with hand function. Previous studies found generally low DASH scores after flexor tendon injuries, 12,26,32,[35][36][37] leaving little room for clinically important changes. For example, by scoring on average 17.0 points at week 13, achieving a clinically important change of 18.8 points 40 was not possible for our patients.…”
Section: Discussionmentioning
confidence: 92%
“…16,34 The DASH has previously been used in studies of patients after flexor tendon injury. 12,26,32,[35][36][37][38] In a study by Wong et al 39 patients at discharge after acute traumatic hand injuries achieved on average 14 (SD 15) DASH points. These results are comparable to our scores, as patients are typically discharged from therapy three months after flexor tendon surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Sadek (2020) found no significant difference in finger mobility after Zone 2B injuries between repairing and not repairing the FDS. Lastly, Natal-Albelo et al. (2020) recently published conclusive findings that FDS excision led to worse short-term functional outcomes (3 months), assessed by TAM, Strickland and DASH, but found no significant differences at 6 months.…”
Section: Discussionmentioning
confidence: 95%
“…Bilateral and comparative measurements of active and passive motion of the involved finger(s) were done with a goniometer on the metacarpophalangeal (MCP), PIP and DIP joints. The clinical outcomes were evaluated using: the total active motion (TAM), TAM percentage relative to the healthy contralateral finger (TAMc) (Natal-Albelo et al., 2020), PIP flexion deformity (degrees), Strickland’s formula (Strickland and Glogovac, 1980) by grouping the ‘excellent’/‘good’ categories and ‘fair’/‘poor’ categories, Tang score (Tang, 2007) by grouping the ‘excellent’/‘good’ categories and ‘fair’/‘poor’/‘failure’ categories. …”
Section: Methodsmentioning
confidence: 99%